"Broken Threads of Varying Colors and Tones": A Souvenir Album of the Phoenix Indian School (1904). (2nd January 2019) - Williams, Nicole
Abstract: In spring 1904, the United States Indian Industrial School in Phoenix, Arizona printed a booklet with ninety-four photographs of campus life and local landmarks for sale to the city's burgeoning tourist market. The Phoenix Indian school's agenda of acculturation, and the racial power relations it reified, permeate the album's representations of Native American students as "civilized" bodies that are uniformly docile and disciplined. However, a careful reading of the photographs alongside the voices of Native pupils opens up alternative meanings incompletely repressed by the institution's photographer. This article weaves student writings from the campus newspaper and other sources back through the album's imagery to identify anonymous children and glimpse their personal stories of growth, struggle, and cultural resilience in the official visual archive of the Indian school. By arguing that the identities and agencies of the Phoenix students can be rediscovered within the limits of the album, this study challenges the conventional interpretation that such pictures simply evidence and enact various forms of oppression, both concrete and symbolic. More broadly, it extends recent scholarly efforts to recover and celebrate those individuals who persevered in federal Indian boarding schools during the era of assimilation.